Role of MANAGE FPO Academy in the Formation and Implementation of Farmer Producer Organizations (FPOs) in India - K.C. Gummagolmath; S. B. Ramya Lakshmi (Journal of Agricultural Extension Management, 2021)
Aggregation of farmers into Farmer Producer Organizations (FPOs) is found to be an effective tool and appropriate mechanism for addressing most of the problems faced by small and marginal farmers in India. There have been a number of interventions to aggregate smallholders by the government, by private and civil society organizations. These include self-help groups, commodity interest groups, contract farming, direct marketing, farmer producer organizations, etc. However, aggregation models have failed to achieve the desired results. Hence, Government of India has come up with the policy to promote new generation Farmer Producer Organizations under its flagship programme of promoting 10,000 such FPOs over the next five years. In implementing this huge task, capacity building is one of the major components wherein, MANAGE has been identified as one of the Institute for implementing this component. In order to achieve this target, MANAGE will support the Government of India. Hence, the National Institute of Agricultural Extension Management (MANAGE) has set up "MANAGE FPO Academy. This paper focuses on the objectives of this Academy, its role in the formation and implementation of FPOs in India, activities and future strategy